Intricately carved Ceiling of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) is comparatively plain and simple, except for the ceiling, which has a square shape with four-armed bharavakas (weight bearers) positioned at each corner. Their upper arms are raised upward to support the roof, while their lower arms carry weapons and an attribute. The square shape of the ceiling transitions into a circle, resembling a full-blown lotus, with a lotus bud hanging from the centre.